Comparison of Clinical Characteristics and Outcomes Between Community-Acquired and Healthcare-Associated Bacteremia Cases due to Bacteroides Species. (4th October 2017) - Ando, Naokatsu; Hayakawa, Kayoko; Katanami, Yuichi; Mezaki, Kazuhisa; Takaya, Saho; Yamamoto, Kei; Takeshita, Nozomi; Kutsuna, Satoshi; Ohmagari, Norio
Abstract: Background: Differences in clinical characteristics and outcomes between community-acquired (CA) and healthcare-associated (HCA) Bacteroides bacteremia cases are not well known. Methods: We evaluated all positive blood cultures between March 2012 and December 2016 in a Japanese 781-bed acute hospital. Identification and susceptibility was performed based on CLSI criteria, and MALDI-TOF has been used since January 2015 in addition to conventional methods. Results: Of 3611 bacteremia cases, 266 (7.4%) were due to obligately anaerobic bacteria, such as Clostridium species ( n = 97 [36.5%]), Fusobacterium species (15 [7.5%]), and Bacteroides species (65 [24.4%]), of which 31 (47.7%) were HCA and 34 (52.3%) were CA. In 22 (33.8%) cases, > 2 blood cultures were positive. B. fragilis was most frequently isolated ( n = 25 [38.5%]), then B. thetaiotaomicron ( n = 9 [13.8%]), B. vulgatus ( n = 5, [7.7%]), B. uniformis ( n = 3 [4.6%]), B. distasonis ( n = 2 [3.1%]), B. ureolyticus ( n = 2 [3.1%]), B. capillosus ( n = 1 [1.5%]), and B . ovatus ( n = 1 [1.5%]). After introducing MALDI-TOF, the number of unidentified Bacteroides species fell from 12 (18.5%) to 5 (7.7%). Sensitivity to ampicillin/sulbactam, cefmetazole, and clindamycin was 85.2%, 92.6%, and 59.3%, respectively. Most bacteremia (51 [78.5%]) were of intra-abdominal origin. Baseline characteristics and immunocompromised status of HCA and CA Bacteroides bacteremia patients were similar, except for diabetes, which was more frequent in HCA cases (Table). There was significantly higher 7- and 30-day mortality in HCA than in CA cases ( P = 0.03). Conclusion: The higher mortality in HCA Bacteroides bacteremia suggests the need for appropriate multidisciplinary management of these cases. Disclosures: All authors: No reported disclosures.